Outcome of Albumin Infusion in Heart Failure Patients (University Heart Journal, 2019)
Background: Heart Failure (HF) is a major public health burden worldwide. Approximately 5 million Americans, 0.4–2% of the general European population and over 23 million people worldwide are living with heart failure. Like few other chronic disease, low serum albumin is common in patients with heart failure (HF). However, very few studies evaluated the outcome of albumin infusion in different stages of HF. Therefore, the objective of this study is to assess the outcome of albumin infusion in heart failure patients.Methods: It was a cross-sectional study. A total of 50 cases of chronic heart failure with reduced ejection fraction and NYHA class III or IV with serum albumin level